2013
DOI: 10.1177/1524839913504586
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Tailored Kiosk-Based Injury Prevention Program in Pediatric Primary Care

Abstract: This study identified behavioral and organizational barriers and facilitators related to the implementation of a clinic-based pediatric injury prevention program. Safe N′ Sound (SNS), an evidence-based tailored injury prevention program designed for pediatric primary care, was implemented in five pediatric clinics in North Carolina. Office managers participated in structured interviews; health care providers participated in focus groups. Waiting room observations were conducted in participating clinics. Qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This article describes organizational and administrative factors related to the outcome of considering Safe N' Sound (SNS) for adoption by children's hospitals in the USA. SNS, developed by the project team and shown in previous work to be efficacious [14][15][16], delivers tailored information to parents of young children to promote the use of needed safety precautions. We describe an innovative approach to developing models for small sample sizes, which is often the case in dissemination research that focuses on organizations as the unit of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This article describes organizational and administrative factors related to the outcome of considering Safe N' Sound (SNS) for adoption by children's hospitals in the USA. SNS, developed by the project team and shown in previous work to be efficacious [14][15][16], delivers tailored information to parents of young children to promote the use of needed safety precautions. We describe an innovative approach to developing models for small sample sizes, which is often the case in dissemination research that focuses on organizations as the unit of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…By tailoring injury prevention counseling, future iterations of SNS-I could be customized for individual home visitation settings, including message concepts and resources for each injury risk deemed important to address for that specific setting. This customizable translation and implementation approach has emerged in previous research as important for promoting adoption of SNS in individual clinic settings (Tse et al, 2013; Weaver et al, 2008). Using this approach would still allow NHVs to provide tailored injury prevention counseling while maintaining a familiar format that may reduce issues related to the environmental audit and printed educational report, increasing the likelihood of adoption and maintenance of this evidence-based program.…”
Section: Discussionmentioning
confidence: 99%
“…We translated SNS for implementation in a pediatric home visitation organization to enhance organizational capacity to address injury prevention effectively and decrease the burden of injury experienced by high-need families. Concurrent to program implementation, qualitative methods were used to explore factors contributing to implementation success and failure (Tse, Nansel, Weaver, Williams, & Botello-Harbaum, 2013). Previous research on the adoption of computer-based programs in health care and community settings has focused largely on measuring their reach or effectiveness, resulting in insufficient data on organizational and behavioral factors related to implementation and maintenance of evidence-based programs (Bergman, Beck, & Rahm, 2009; Kreuter, Alcaraz, Pfeiffer, & Christopher, 2008; Trinks, Festin, Bendtsen, & Nilsen, 2010; Walton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Typical injury prevention intervention evaluates the effectiveness by measuring outcomes such as knowledge, attitude and safety behaviour but it is important to note the sustainability of the education intervention in term of satisfaction of delivery methods, timing and relevance of the topic to the targeted population. Evidence has shown that injury prevention intervention program would be more sustainable in term of support from the medical staff if the patients are highly satisfied and have high perceived value on the program (21).…”
Section: Features Of the Intervention Methods Of Deliveriesmentioning
confidence: 99%